2015
DOI: 10.4236/jep.2015.61006
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of Lead Adsorption on Zeolites

Abstract: The adsorption of Pb on zeolites A4, X, Y and mordenite was studied at various initial pH with the purpose of assessing the pH dependence of Pb adsorption. The adsorption was conducted using 0 -0.6 mM Pb(NO3)2 in the presence of 100 mM NH4NO3 and pH adjustment done using HNO3. The coexisting NH4NO3 served as a representative of other cations available in nature. The study was conducted at initial solution pH ranging from 3 -5. Adsorption results were analyzed using Langmuir isotherm analysis. Adsorption was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…A number of reports (Kabwadza-Corner et al, 2015;Krol, 2020) indicated that the most important characteristics of zeolite are its surface area and crystal structure. Zeolite has a complex three dimensional network of tetrahedrous SiO4 and AlO4 -which creates lattices or cavities that can trap various ionic pollutants and organic molecules (Atikah, 2017;Belova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports (Kabwadza-Corner et al, 2015;Krol, 2020) indicated that the most important characteristics of zeolite are its surface area and crystal structure. Zeolite has a complex three dimensional network of tetrahedrous SiO4 and AlO4 -which creates lattices or cavities that can trap various ionic pollutants and organic molecules (Atikah, 2017;Belova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…14) The K + adsorbed zeolite sample was exchanged again with NH 4 + ions using a 1 M NH 4 Cl solution. The CEC was determined by measurement of the K + ion concentration in a desorbed and washed solution by atomic absorption spectrometry (Hitchi ZA 3300).…”
Section: Methodsmentioning
confidence: 99%
“…2) Zeolites have adsorption capacity for heavy metals adsorption such as copper 3) and lead, 4) as well as for silver ion. 5) Many studies were focused on silver exchanged zeolites, due to their function as catalyst, for example Ag exchanged ZSM-5 as catalyst for CO oxidation, 6) or photocatalytic decomposition of NO into N 2 and O 2 , 7) or silver doped zeolite Y as antibacterial.…”
Section: Introductionmentioning
confidence: 99%